Keefektifan Teknik Cinema Therapy untuk Meningkatkan Sikap Altruistik Siswa Kelas VIII DI SMPN 1 Gondanglegi Kabupaten Malang - Tresyana Maretha; Romia Hari Susanti; Eva Kartika Wulan Sari (JKI (Jurnal Konseling Indonesia), 2020)
Altruism is a voluntary action taken by a person or group of people to help others without expecting anything in return. This study aims to test the Effectiveness of Cinema Therapy Techniques to Improve the Altruistic Attitudes of SMPN 1 Gondanglegi Students in Malang Regency. This research is an experimental study with a one-group pretest-posttest village design and uses a Likert scale instrument. The sample of this study is junior high school students who have low altruistic attitude criteria by choosing through quota sampling technique where students who meet only the criteria will be selected, Wilcoxon Sign Rank Test data analysis, research showing the results of sig. (2-tailed) is 0.012 which indicates that 0.012 <0.05, which means that cinema therapy technique is effective to improve the altruistic attitude of VIII grade students of SMP N 1 Gondanglegi Malang Regency which is subjected to truth and can be accepted at a significant level of 5%.